Annular Lichenoid Dermatitis (of Youth) - Giorgio Annessi; Emanuele Annessi (MDPI AG, 2022)
About 20 years after its first description, Annular Lichenoid Dermatitis of Youth (ALDY) is recognized as a distinctive lichenoid dermatosis with specific clinical and histological features. The disease occurs mostly in young persons all over the world, runs a chronic course, and has an obscure etiopathogenesis. Clinically, lesions consist of persistent, asymptomatic erythematous macules and round-oval annular patches with a red-violaceous non-scaling border and central hypopigmentation, mostly localized on the groin and flanks. Histology shows a peculiar lichenoid dermatitis characterized by irregular epidermal hyperplasia with an alternation of thinned and quadrangular rete ridges and a dense band-like lichenoid infiltrate of lymphocytes in the papillary dermis. Typically, there is infiltration of lymphocytes into the lower epidermal layers with massive necrosis/apoptosis of keratinocytes, which is limited to the tips of rete ridges. Dermal lymphocytes are usually CD3+, CD4+, while most of the intraepidermal T cells are CD8+. Analysis of TCR-γ-chain gene rearrangement displayed polyclonality in all cases examined. Differential diagnosis mainly includes morphea, mycosis fungoides, annular erythemas and inflammatory lesions of vitiligo. Topical corticosteroids and topical tacrolimus represent the most effective drugs for ALDY treatment.